Dyke-Davidoff-Masson Syndrome (DDMS) in Adult: A Rare Case in Rural Area - Indra Pramanasari (Universitas Airlangga, 2023)
Highlight: Dyke-Davidoff-Masson syndrome (DDMS) is an uncommon neurological disease defined as cerebral hemiatrophy with a contralateral motor deficit, facial asymmetry, and seizures. The proper diagnosis and early causative treatment significantly improve the outcome of thee disease. ABSTRACT Introduction: Dyke-Davidoff-Masson syndrome (DDMS) could be a rare neurological disorder characterized by cerebral hemiatrophy and an engine shortfall on the contralateral side of the body. Furthermore, facial asymmetry and seizures are common symptoms. Classic imaging findings in individuals with DDMS are ventriculomegaly, cerebral hypoplasia, paranasal sinus hyperpneumatization, and compensatory osseous broadening. The relationship between symptoms and imaging findings is used to determine DDMS. Case: A 46-year-old female patient arrived at the hospital with an inability to speak three days before admission, refused to eat or drink, and had a fever. She also had a slanted mouth and right-sided hemiparesis with a history of seizures. A firm boundary consolidation on the right pericardium was found on the chest X-ray, suggesting pulmonary TB. On a non-contrast head CT scan, thickening of the left hemicalvaria was found, accompanied by a widening of the left frontal-ethmoidal sinus, hyperpneumatization of the left mastoid air cell, and left cerebral hemiatrophy, all accompanied by left lateral ventricular dilatation. Conclusion: The proper diagnosis and early causative treatment significantly improve the outcome of the disease.